2016
DOI: 10.1097/xce.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Core body temperature is lower in postmenopausal women than premenopausal women: potential implications for energy metabolism and midlife weight gain

Abstract: Objective Weight gain during the menopausal transition is common. Although studies have suggested that weight gain is more likely related to aging than menopause, there is a reduction in resting energy expenditure with surgical or natural menopause which is independent of age and changes in body composition. The underlying mechanisms could include a reduction in core body temperature. Methods Data were obtained from two related studies. Sample size was 23 men and 25 women (12 premenopausal,13 postmenopausal)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A 6 month follow-up assessment would have assessed whether changes are maintained over time. Female menstrual patterns may impact core body temperature; however only 1 female was pre-menopausal and reported a regular 28-d menstrual cycle and post-menopausal women may have more stable temperature rhythms [ 40 ]. The one menstruating female was tested in the follicular phase at baseline prior to SRT and during follicular post therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A 6 month follow-up assessment would have assessed whether changes are maintained over time. Female menstrual patterns may impact core body temperature; however only 1 female was pre-menopausal and reported a regular 28-d menstrual cycle and post-menopausal women may have more stable temperature rhythms [ 40 ]. The one menstruating female was tested in the follicular phase at baseline prior to SRT and during follicular post therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Footbath is a simple and low-cost intervention that can be easily used by menopausal women to alleviate sleep problems. The skin temperature, circadian rhythm, and core body temperature (rectal temperature) have a functional association with the sleep/ wakefulness cycle (Neff et al, 2016). The core body temperature starts to increase in the morning and achieves its maximum in the afternoon.…”
Section: Introductionmentioning
confidence: 99%
“…Patients had improvements regardless of their age and the age of menopause. In a previous study, the factors significantly related to ≥3% weight gain were weight change in the past 2 years, age at menopause, dietary fiber, fat, alcohol intake, and smoking [42].…”
Section: Discussionmentioning
confidence: 93%
“…Several papers have demonstrated that aging is the primary driver of FM gain in menopausal women, rather than the constant change of hormone levels during menopause [39,40]. A reduction in BMR at menopause has been shown to be independent of changes in BC [41] and may be related to a reduction in the 24-h core temperature [42].…”
Section: Discussionmentioning
confidence: 99%